The Effect of Common Knowledge Construction Model-Based Instruction on 7th Grade Students’ Academic Achievement and Their Views about the Nature of Science in the Electrical Energy Unit at Schools of Different Socio-economic Levels - Caymaz, Belkiz; Aydin, Abdullah (Springer Science and Business Media LLC, 2020)
The aim of this study is to investigate the effectiveness of the common knowledge construction model (CKCM)-based instruction on academic achievement and 7th grade students’ views about the nature of science (NOS) presented in electrical energy unit at schools of different socio-economic levels. In accordance with this purpose, three secondary schools at different socio-economic levels (lower, middle and upper) in Kastamonu Province, Turkey, were selected. One experimental group and one control group were randomly selected from schools at each socio-economic level. The teaching interventions in all groups lasted for 6 weeks (24 class-hours). While the lessons of the experimental group were taught with the activities developed in accordance with the CKCM, the lessons of the control group were taught in compliance with the 2013 Science Curriculum. As a result of this study, it was observed that the CKCM-based instruction increased students’ level of academic achievement and ensured the permanence of the knowledge learned. In terms of academic achievement, no significant difference was observed between the schools at the lower and middle socio-economic levels and the schools at middle and upper socio-economic levels. However, a significant difference between the schools at the lower and upper socio-economic levels was observed in favor of the upper socio-economic level school. Moreover, the CKCM-based instruction had a positive effect on the students’ views on the nature of science.
Keywords: 4. Education; 3. Good health